PENGARUH PENGGUNAAN TEPUNG YANG BERBEDA TERHADAP KUALITAS ORGANOLEPTIK DAN KIMIA BAKSO DAGING SAPI ONGOLE BETINA AFKIR (The effect of using different flour on organoleptic and chemical quality of meatball of ongole beef culled) - Maubere, Devan Oscalis; Noach, Yakob R.; Malelak, Gemini E. M. (JURNAL NUKLEUS PETERNAKAN, 2024)
This study aims to find out how the effect of using different flour on organoleptic and chemical quality of bakso of ongole beef culled. The test design that used in this study is completely randomized design (CRD) with 4 treatments and 3 replications. The treatments consisted of P0 = 100% Tapioca, P1 = 70% Tapioca + 30% Taro flour, P2 = 70% Tapioca + 30% Purple sorghum flour, and P3 = 70% Tapioca + 30% Purple yam flour. The parameters tested including water content, protein content, fat content, and organoleptic quality including taste, texture, scent, and color. Analysis of variance results showed that the treatments had a very significant effects (P<0,01) to water content, protein, fat, taste, color, texture, and scent. It can be concluded that using different flours produces bakso with different chemical qualities and organoleptic. Bakso that produced at P0, P1, P2, and P3 treatments had water and protein content that fulfilled SNI standard. For organoleptic, the best treatment was P1 treatment because it had highest rating score in the taste, color, texture, and scent section, when compared to the P2 and P3 treatments.